Analysing Transportation Data with Open Source Big Data Analytic Tools - Yogesh Beeharry; Tulsi Pawan Fowdur; Visham Hurbungs; Vandana Bassoo; Vidasha Ramnarain-Seetohul (IAES Indonesian Section, 2017)
Big data analytics allows a vast amount of structured and unstructured data to be effectively processed so that correlations, hidden patterns, and other useful information can be mined from the data. Several open source big data analytic tools that can perform tasks such as dimensionality reduction, feature extraction, transformation, optimization, are now available. One interesting area where such tools can provide effective solutions is transportation. Big data analytics can be used to efficiently manage transport infrastructure assets such as roads, airports, bus stations or ports. In this paper an overview of two open source big data analytic tools is first provided followed by a simple demonstration of application of these tools on transport dataset.